CONTRIBUTION OF MAQASID AL-SYARIAH TO THE UMMAH SUSTAINABILITY: THE STUDY OF THEORY "I'TIB?R AL-MA?L?T" AND "MUR? '?T AL-KHUSH?SHIY?T". - MUHAMMAD AMIN, ABD RAUF (Human Sustainability Procedia, 2018)
The human issue is a very central issue in all Islamic studies. In Islam, The human case as the study of the object of law occupies the second position after the study of the law itself. That is why, scholars are often positioned as a bridge that is expected to negotiate human interests to the creator. For that purpose, in the light of al-Quran and al-Sunna scholars have reconstructed a number of legal systems to maintain the continuity and sustainability of human beings. Islam from the beginning was aware that the laws of God would not be able to be applied without human survival. Therefore, Islam then establishes human sustainability as an important part of Maqasid al-Shariah and Islamic law is often forced to be synchronized through out the human interest that can ensure its survival. This article aims to know exactly how the science of Maqasid al-Shariah works in guarding the continuity of humans as well as the theories of Maqasid regarding with the issue of human sustainability in addition to the terminology of Hifz al-Nasal and Hifz al-Nafs. However these two theories are very abstract. So in addition to these two terminology there are a number of Maqasid theories which are indicated as supporting theories and applicable to this issue especially the theories of "I'tib?r al-Ma?l?t" and "Mur? '?t al-Khush?shiy?t". The first necessitates every application of the law to consider the impact it will incur for human benefit while the latter ensures that Islamic legal applications take into account the realistic specifications held by society or people who will accept the application of the law. The method used in this study is Library Research by exploring the theories relating to various Islamic legal literature and Maqasid al-Shariah.. The results of the imperical studies show that these two theories have contributed significantly to the continuity of the teachings of Islamic law.